Experiences of low iodine diets in the treatment of differentiated thyroid cancer with radioactive iodine ablation therapy. (October 2020) - Herbert, Georgia; Searle, Aidan; England, Clare Yvonne; Ness, Andy; Beasley, Matthew; Haupt-Schott, Ingrid; Moss, Laura; Wescott, Judith; Atkinson, Charlotte
Summary: Background and aims: International guidelines on the treatment of differentiated thyroid cancers (DTC) promote the use of low iodine diets (LID) prior to radioactive iodine remnant ablation (RIA), as high iodine status may interfere with radioiodine uptake. Most UK treatment centres adhere to these guidelines and advise people to consume a LID. There is limited research as to how people cope with the LID or its impact on daily life and wellbeing, and no studies have been conducted in the UK. This study explored peoples' views and experiences in relation to consuming a LID during treatment for DTC with RIA. Methods: Twenty-eight semi-structured interviews were conducted with people from across three treatment centres where differing advice had been delivered regarding a LID. Interviews were recorded, transcribed verbatim and key themes were developed through inductive thematic analyses. Results: Individuals advised to consume a LID believed that adhering to the diet would help their treatment. Most restricted their diets beyond what was recommended and there was confusion surrounding what they could eat as part of the diet. Food selection and preparation were important which included substitution of foods and ingredient checking. Being on the diet was considered to have both a physical and psychological impact. Conclusions: The findings of this study provide a qualitative insight into the lived experiences of people with DTC in relation to consuming a LID. The results have relevance for professionals providing dietary guidance at oncology centres treating patients with RIA therapy in the UK.